2014
DOI: 10.1002/anie.201400323
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanoflowers for Multiplexed Cellular Imaging and Traceable Targeted Drug Delivery

Abstract: We present a facile approach to make aptamer-conjugated FRET (fluorescent resonance energy transfer) nanoflowers (NFs) through rolling circle replication for multiplexed cellular imaging and traceable targeted drug delivery. The NFs can exhibit multi-fluorescence emissions by a single-wavelength excitation as a result of the DNA matrix covalently incorporated with three dye molecules able to perform FRET. Compared with the conventional DNA nanostructure assembly, NF assembly is independent of template sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
243
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(249 citation statements)
references
References 33 publications
5
243
0
1
Order By: Relevance
“…The template can be customized so that the DNA product includes functional sequences such as DNA aptamers, DNAzymes, spacer domains, restriction enzyme sites and G-quadruplexes. [26][27][28] The AS1411 aptamer specifically recognizes nucleolin, which is overexpressed in various cancer cells, including breast cancer, lymphocytic leukemia, hepatocellular carcinoma, prostate carcinoma and renal cell carcinoma. 25 We expected that the numerous aptamers in the elongated ssDNA would enhance the binding of the DNFs to target cells through multivalent interaction with the nucleolin.…”
Section: Construction and Characterization Of The Dnfsmentioning
confidence: 99%
“…The template can be customized so that the DNA product includes functional sequences such as DNA aptamers, DNAzymes, spacer domains, restriction enzyme sites and G-quadruplexes. [26][27][28] The AS1411 aptamer specifically recognizes nucleolin, which is overexpressed in various cancer cells, including breast cancer, lymphocytic leukemia, hepatocellular carcinoma, prostate carcinoma and renal cell carcinoma. 25 We expected that the numerous aptamers in the elongated ssDNA would enhance the binding of the DNFs to target cells through multivalent interaction with the nucleolin.…”
Section: Construction and Characterization Of The Dnfsmentioning
confidence: 99%
“…A cationic delivery vehicle or nanostructured DNA is required for intracellular detection. [32][33][34] Since nano-sized GO is readily internalized by mammalian cells, GO-based sensors can be directly used for intracellular detection. 35,36 Furthermore, GO protects adsorbed DNA from degradation by nucleases, 37 which is also important for detection in biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar approach with nanoparticles, Zheng et al (38) conjugated aptamers to gold nanospheres and hybridized aptamer-recognition elements using nanoflare techniques to achieve sensing for intracellular molecules, such as adenosine triphosphate (ATP), the most important molecule regulating cellular metabolism. Hu et al (39) reported using another aptamer-nanomaterial complex (known as DNA nanoflowers) to perform cell imaging and drug-delivery tracing in cells. These…”
Section: Aptamer-based Biosensorsmentioning
confidence: 99%